2021
DOI: 10.1038/s43247-021-00125-7
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification is the major nitrous acid production pathway in boreal agricultural soils

Abstract: Nitrous acid (HONO) photolysis produces hydroxyl radicals—a key atmospheric oxidant. Soils are strong HONO emitters, yet HONO production pathways in soils and their relative contributions are poorly constrained. Here, we conduct 15N tracer experiments and isotope pool dilution assays on two types of agricultural soils in Finland to determine HONO emission fluxes and pathways. We show that microbial processes are more important than abiotic processes for HONO emissions. Microbial nitrate reduction (denitrificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
(128 reference statements)
0
20
0
Order By: Relevance
“…The low HONO and NO emissions in the vegetated surfaces (⩽0.2 µg N m −2 h −1 ; figure 3(a), table S1) were associated with lower mineral N content than in the unvegetated surfaces (F(1,37) = 5.47, P = 0.0248). The HONO emissions measured from permafrost peatlands are smaller than the global median (18 µg N m −2 h −1 ) (Bhattarai et al 2021), but within the range reported for boreal peatlands drained for agriculture (1.7-6 µg HONO-N µg m −2 h −1 ) (Maljanen et al 2013). Notably, the mean NO emission from the unvegetated peat surfaces of the highest emitting Seida site (59.3 µg N m −2 h −1 ; table S1) is almost two-fold the global mean NO emission (30.8 µg N m −2 h −1 ) (Davidson and Kingerlee 1997) and more than two-fold the mean N 2 O emission (24.8 µg N m −2 h −1 ) from peatlands across the permafrost region (Voigt et al 2020), highlighting the importance of this newly revealed N gas emissions from Arctic permafrost peatlands.…”
Section: Magnitude and Drivers Of Hono And No Emissionsmentioning
confidence: 80%
See 4 more Smart Citations
“…The low HONO and NO emissions in the vegetated surfaces (⩽0.2 µg N m −2 h −1 ; figure 3(a), table S1) were associated with lower mineral N content than in the unvegetated surfaces (F(1,37) = 5.47, P = 0.0248). The HONO emissions measured from permafrost peatlands are smaller than the global median (18 µg N m −2 h −1 ) (Bhattarai et al 2021), but within the range reported for boreal peatlands drained for agriculture (1.7-6 µg HONO-N µg m −2 h −1 ) (Maljanen et al 2013). Notably, the mean NO emission from the unvegetated peat surfaces of the highest emitting Seida site (59.3 µg N m −2 h −1 ; table S1) is almost two-fold the global mean NO emission (30.8 µg N m −2 h −1 ) (Davidson and Kingerlee 1997) and more than two-fold the mean N 2 O emission (24.8 µg N m −2 h −1 ) from peatlands across the permafrost region (Voigt et al 2020), highlighting the importance of this newly revealed N gas emissions from Arctic permafrost peatlands.…”
Section: Magnitude and Drivers Of Hono And No Emissionsmentioning
confidence: 80%
“…humic acid) into gaseous NO and N2O in the process called chemo-denitrification (green arrow) (Coby and Picardal 2005). Nitrite can also react chemically with proton (H + ) to form HONO and NO (Cleemput and Samater 1995, Su et al 2011, Bhattarai et al 2021. The italic terms above the colored arrows indicating nitrogen transforming processes denote the genes encoding enzymes carrying out the respective processes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations